Immediate and Decisive Political Action is Needed to Strengthen Social Debt Counselling - Ines Moers (Wirtschaftsdienst)
Abstract The social benefit of debt counseling is undoubted. Those seeking advice are empowered to claim their consumer rights and (regain) their quality of life. Existential emergencies can be avoided and significant savings can be made for the national budget. It also benefits creditors financially by avoiding private insolvency. In order to strengthen debt counselors, clear and immediate political action is required. One step should be the introduction of a legal right to debt counselling and the expansion of counseling capacities. Both could be financed through fair creditor participation and would be accompanied by a nationwide initiative to train new debt counselors.